Analysis of Planning for Health Workforce Needs at Lasinrang Pinrang Regional General Hospital - Abdillah, Abdillah; Harum, Habil; Jumadi, Handani; Pratiwi, Siska Wijayanti (Journal of Community Health Provision, 2024)
Hospital is a health service unit as a place where hospital personnel perform their main tasks and functions. Integration between hospitals and health workers is closely related in terms of health services. How the face of the hospital depends on the quality of its health workers. This research is descriptive research. Research location at the Health Service Office of Lasinrang Pinrang Regional General Hospital. The study was conducted from May 7, 2021 to July 7, 2021. The population in this study were all health workers at the Health Service Office of the Lasinrang Pinrang Regional General Hospital with a sample size of 22 respondents. The results of the study indicate that the Inventory of new health workforce resources is limited to the type and number, while others are not yet such as the skills and abilities of each existing health worker. The forecast of health workforce resources that has been carried out is only informal and immediate, and this is not a systematic planning effort.  The suggestion in this research is that there needs to be team work or specialist planning staff or a section/department in the organizational structure. which deals with human resource planning and development and the need for the formulation of strategic plans to serve as a basis/reference for planning health workforce resources.